Sustainability in Family Businesses: The Case of Ermelinda Freitas - Carvalho, L.; Paiva, I.; Gavancha, I. (IX International Congress on Teaching Cases related to Public and Nonprofit Marketing, 2017)
Students seldom contemplate the importance of sustainability in family businesses. Indeed, the economic dimension of sustainability using performance statements remains a neglected field of study. The case of a Portuguese family firm in the wine sector, Casa Ermelinda Freitas, is used to introduce students to sustainability analyses through the study of the company's financial information. This provides instructors with an opportunity to discuss the actual financial state of the company and how to improve some indicators, as well as to present an overview of the long term sustainability of a family business. A qualitative methodology is used based on the documental analysis of financial reporting statements and information collected from the company's website and the media. This case can be used in management and accounting classes at both the bachelor and master levels. It is an important topic for users of financial information, entrepreneurs and other stakeholders concerned with these issues.